A standardized 3U CubeSat common bus architecture for improving mission success - Gayle, Jeremiah B., author; Bradley, Thomas H., advisor; Cale, James, committee member; Herber, Daniel, committee member; Ravich, Josh, committee member; Reising, Steven, committee member (Colorado State University. Libraries, 2026)
CubeSats are a class of nanosatellites that use a standardized form factor called "one unit" (1U). Each 1U measures 10 × 10 × 10 cm and enables scalable configurations. Common CubeSat sizes include 1U, 1.5U, 2U, 3U, and 6U; larger variants up to 12U and 27U. The small form factor of CubeSats enables low-cost science missions and on-orbit technology demonstrations. However, CubeSats have historically exhibited high failure rates and are therefore not viewed as reliable platforms for high-value science missions. This research examines whether the CubeSat failure rate can be reduced through systems engineering with the development of a 3U common bus. The 3U common bus is characterized, designed, tested, and integrated into the CubeSat design process to improve performance and enable higher reliability. In this research, past CubeSat missions were examined to determine whether identifiable trends exist in subsystem failures, including failure mechanisms and contributing factors. Following a systems engineering methodology, each CubeSat failure was examined to determine whether deficiencies in verification and validation (V&V) and integration and test (I&T) activities prior to launch are associated with observed failures. A set of requirements was derived based on the findings, and a notional 3U common CubeSat bus design is proposed with the goal of increasing mission success and reducing subsystem failures. A baseline schedule was developed for a standard CubeSat systems engineering development process and compared to the schedule for a 3U common bus-enabled CubeSat. The results demonstrate that CubeSat failures are concentrated within the electrical power system (EPS), communications system (COM), and on-board computer (OBC), which together account for the majority of reported on-orbit failures. Reported failure mechanisms include battery thermal degradation, solar array deployment faults, antenna deployment failures, and radiation-induced single-event upsets. These subsystem failures are strongly correlated with deficiencies in V&V and environmental testing, with as many as 65% of CubeSat missions forgoing at least one of the following vibration testing, thermal vacuum testing, or end-to-end RF testing due to schedule and resource constraints. Collectively, these findings demonstrate that CubeSat failures are driven less by inherent subsystem limitations and more by systemic gaps in systems engineering discipline, integration practices, and V&V execution gaps that a standardized, pre-qualified 3U common bus architecture is designed to address. The development of a 3U common bus provides stakeholders with tools and methods for accelerating development while improving reliability. The practical implication is that CubeSat development can transition from bespoke bus integration to a payload-centric model, improving reliability and mission value without proportionally increasing cost. This dissertation argues that early CubeSat failures concentrate in a small set of subsystems (EPS/COM/OBC) in large part because schedule pressure compresses integration, verification, and end-to-end testing. A standardized, pre-qualified 3U common bus is proposed as the intervention to reduce custom integration variability and return schedule margin. The measurable outputs are increased testing time (environmental, functional, and RF) and reduced late-cycle integration cycles, which together are expected to reduce early on-orbit failure rates and improve mission success.